Decreased desire to have children: A qualitative study - Maryam Ghaderi Najafabadi; Zahra Shojaei Ardekani; Samira Sohbati; Firoozeh Mirzaee; Masoumeh Ghazanfarpour; Sahebeh Dadshahi (Asian Pacific Journal of Reproduction)
Objective: To explain barriers to childbearing among working women from the perspective of working women and midwives. Methods: In this study, a qualitative study of content analysis method was employed. The study was conducted from December 2021 to July 2022. The population consisted of working women and midwives. Data collection was conducted using semi-structured interviews and continued until data saturation was achieved. Through purposeful sampling, 10 women and 11 midwives were selected as the sample. The data were analyzed by Graneheim and Lundman content analysis approach. For more rigorous, Nvivo 14 software was also used for data management, analysis, coding and organization of data. Results: This study included 21 women (10 women employees and 11 midwives) aged 25-43 years (for women employees) and 2756 years (for midwives) with 1 to 34 years of job experience. In examination of participant’ views about the barriers to childbearing, 1 124 codes were identified, of which we managed to extract six subthemes and two themes. Two themes emerged: “lack of social support and lack of family support”. Subthemes of “lack of social support” were “inadequate leave, long distance from workplace, and insufficient wages”. Subthemes of “lack of family support” were “lack of spouse support, lack of spouse's family support, and lack of their family support”. Conclusions: Different socioeconomic factors influence childbearing tendency in working women. Social and family supports play an important role in this regard. It is important to take these factors into account at the time of policymaking in the field of midwifery.